Filtering the clots during pregnancy - experience at a tertiary centre. (18th April 2012) - Anbazhagan, A; Harper, A; Hunter, A; Bailie, C; Benson, G; Ellis, P; Collins, A; Kennedy, P
Abstract : Background: According to the Centre for Maternal and Child enquiries report (2006-08), thrombosis and thromboembolism accounted for eighteen maternal deaths (0.79/100 000 maternities). Of these most were due to pulmonary embolism (PE). Majority of the cases of PE are preventable by appropriate thromboprophylaxis. Inferior venacaval (IVC) filters are usually indicated if thromboembolism recurs despite adequate anticoagulation, if anticoagulant therapy is contraindicated or when there is proximal deep vein thrombosis (DVT). Methods: This was a retrospective review of case records, of women who had an IVC filter inserted during pregnancy or postpartum period over fourteen years (1997-2010). Results: IVC filters were inserted in 14 patients, one of which was during the postnatal period. Four of these patients suffered from pulmonary embolism and the others had extensive proximal DVT. Three patients had Factor V Leiden mutation. All the patients had a retrievable filter placed. Sixty four percent of these were placed in the suprarenal position accessed through the internal jugular or right femoral vein. The average gestation at delivery was 39 weeks. Eight babies were delivered by caesarean section. Filters were retrieved successfully in 57% of the women whilst the others were advised to continue lifelong warfarin. The average hospital stay was 20 days. All maternal and neonatal outcomes were good. Five of these patients had 6 subsequent uncomplicated pregnancies and deliveries. Conclusion: Retrievable IVC filters are valuable in preventing life threatening PE in susceptible pregnant women; however potential difficulty in retrieval necessitating long term warfarin therapy is a possible complication.